Unionized Workforce and Employee Well-Being: A Comparative Study of Psychological Safety in Unionized vs. Non-Unionized Organizations - Sundari, Pipit; Pertiwi, Dyah Nurul Bayu; Nugroho, Bayu Sapta Adi (SAFE-Network, 2025)
This study explores the relationship between unionization and psychological safety as a determinant of employee well-being, using a qualitative comparative approach. By analyzing interviews with employees from both unionized and non-unionized organizations, the research identifies key differences in how institutional structures shape perceptions of voice, protection, and trust in the workplace. Findings reveal that unionized environments promote higher levels of psychological safety through formal grievance mechanisms, consistent managerial practices, and collective representation, enabling employees to express concerns without fear of retaliation. In contrast, non-unionized settings are often characterized by ambiguity, interpersonal dependency, and limited institutional safeguards, contributing to lower psychological security. The study contributes to the theoretical expansion of psychological safety by situating it within organizational systems and suggests practical strategies for enhancing employee voice and well-being across diverse organizational contexts.